Complexes of dextran sulfate and anthocyanins from Vaccinium myrtillus: Formation and stability. (20th September 2015) - Klimaviciute, Rima; Navikaite, Vesta; Jakstas, Valdas; Ivanauskas, Liudas
Highlights: Complexes between DESU and anthocyanins (ATC) from wild bilberries were formed. 1.7 g of ATC per g of DESU could be introduced into a complex. Formation of complexes was confirmed by FT-IR. Individual ATC incorporated into a complex were determined by HPLC. ATC introduced into the complex showed the higher stability and antioxidant activity. Abstract: To improve the stability and antioxidant activity of anthocyanins (ATC), complexes of dextran sulfate (DESU) and ATC extracted from Vaccinium myrtillus were formed during electrostatic interaction between sulfo groups of DESU and cationic moieties of ATC. At the optimal weight ratio DESU/ATC = 0.4 g/g, the amount of ATC introduced into a complex depended on the total concentration of the reagents. About 1.7 g of ATC per g of DESU could be incorporated into a complex. The formation of DESU/ATC complexes was confirmed by HPLC and FT-IR spectroscopy. According to HPLC analysis, the amount of individual ATC incorporated into a complex varied from 73.7% in the case of malvidin-3-O-glucoside to 90.8% in the case of delphinidin-3-arabinoside.